Sensitization and Serological Biomarkers in Knee Osteoarthritis Patients With Different Degrees of Synovitis. Issue 10 (October 2016) - Petersen, Kristian K.; Siebuhr, Anne S.; Graven-Nielsen, Thomas; Simonsen, Ole; Boesen, Mikael; Gudbergsen, Henrik; Karsdal, Morten; Bay-Jensen, Anne C.; Arendt-Nielsen, Lars
Abstract : Objective: Synovitis is a frequent condition in knee osteoarthritis (KOA) and has been associated with pain. This study investigated the links between the pressure hyperalgesia, the clinical pain, the degree of the synovitis, inflammatory biomarkers, and tissue-specific biomarkers in KOA patients. Materials and Methods: Fifty-eight KOA patients and 33 pain-free controls participated in this study. The patients were magnetic resonance imaging scanned, and the Boston-Leeds OA Knee Score (BLOKS, 0 to 3) was used to assess the degree of synovitis. The maximal knee pain intensity over the last 24 hours was scored on a visual analog scale (VAS). The pressure pain thresholds (PPTs) were assessed over the KOA-affected knee. Serological biomarkers were measured in fasting serum: high-sensitive C-reactive protein, matrix metalloproteinase–mediated degradation of CRP, and matrix metalloproteinase–mediated collagen type I, II, and III degradation (C1M [connective tissue], C2M [cartilage], C3M [synovial membrane]). Results: Compared with controls, the KOA patients showed increased levels of C1M ( P <0.02), C2M ( P <0.001), and high-sensitive C-reactive protein ( P <0.02), decreased level of C3M ( P <0.03), and reduced PPTs ( P <0.03). Patients with no (BLOKS 0) and moderate to severe (BLOKS 2&3) synovitis had significantly lower PPTs compared with mild synovitis (BLOKS 1). Significantly negative correlations were found between VAS and PPTs. No correlations were found between BLOKS and the VAS, PPT, or biomarkers. Discussion: Patients without and with moderate to severe synovitis demonstrated local pressure hyperalgesia and increased degrees of: (1) systemic inflammation, (2) connective tissue degradation, (3) cartilage degradation, and (4) decreased synovial membrane degradation as compared with controls.